Pengaruh Pendidikan dan Pelatihan, Motivasi dan Lingkungan Kerja Terhadap Kinerja Guru - Alfiyan, Riska Silfi; Damayanti, Damayanti (UMSU, 2024)
This observation uses a saturated sample to prove the impact of Education and Training, Encouragement, and Workplace on Teacher Performance at Junior High School 1 Sulang. This observation used the survey method at the research object to collect data; questionnaires were distributed to 42 informants, consisting of all teachers at Junior High School 1 Sulang. Data analysis of respondents was carried out using multiple linear regression analysis. The conclusion of this observation suggests that education and training (DIKLAT) has a positive and significant effect on teacher performance; motivation has a negative and significant effect on teacher performance; and workplace has a positive and insignificant effect on teacher performance. The independent factors of education and training, motivation, and teacher performance account for 54.4% of the variation in the dependent variable, teacher performance, with an adjusted R square of 0.544.